Resource use efficiency analysis in strawberry production in selected areas of Bangladesh - Khatun, M; Rashid, MA; Khandoker, S; Kundu, ND; Matin, MA (SAARC Journal of Agriculture, 2019)
Inefficient use of existing scarce resources has adverse effect on food production and production cost hence, low income among the farmers across the nation. Strawberry farming is profitable but costly. So the study was designed to explore resource use efficiency of strawberry cultivation in Rajshahi and Joypurhat district of Bangladesh. Primary data were collected from 100 strawberry growing farmers. Data were analyzed by using descriptive statistics, Cobb-Douglass production function and marginal productivity analysis. The results showed that 41% farmers were 18 to 30 years old. Highest 26% farmers had primary level of education, 61% farmers had small farm, and 69% farmers had 1 to 3 years’ experience of strawberry cultivation. The double log function showed the best fit with adjusted R2 of 61%. Production inputs such as sapling and fertilizer had positive and labour and chemicals had negative and significant effect on outputs. Sapling, land and water were underutilized and labour, cowdung, fertilizer and chemicals were over used. About 37% farmers reported that strawberry plants were attacked by many more diseases. Approximately, 48% farmers reported that transportation facilities of the study areas were poor. Efficiency ratio of the inputs indicates, farmers of the study area were not efficient in using inputs and it is needed to adjust resource use in order to improve farm profit at this level of technology used. The study also recommends that the farmers need training to be efficient. SAARC J. Agri., 17(1): 189-200 (2019)